(3GdTLQI GdfYeGfjI heYgG OGFQJgGs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3Ydi Hf GdedG YHGOi Hf edG CMeO Hf edG UGdM Hf edG eMeO GdRjdi GdgjGHi s)
(3ChdgG (B:s
(3ZdHJ GdQhe ai COfi GdCQV hge ef HYO ZdHge SjZdHhf ai HVY Sfjf ddg GdCeQ (B" s
(3BNQgG (B:s
(3hbO JbOe GdJfHjg Ydi aQhY GdTLQI GdfYeGfjI hgfG Je HJeGegG hde jHb EdG CMcGe GdbQBf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B41s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds